Duration of Trastuzumab. In matters of the heart, one size may not fit all?. Issue 13 (September 2015) - Simmons, Christine; Dent, Susan; Brezden-Masley, Christine
Abstract The PHARE trial was initially reported in 2013 and demonstrated that 6 months of Trastuzumab therapy was inferior to 12 months of therapy in terms of reducing risk of Her2+ breast cancer recurrence. Updated results of this study have been presented and demonstrate that while there is a reduction in breast cancer risk with 12 months of therapy, there is an increase in risk of cardiac events. This may have implications for patient selection, and certainly has implications for future studies. As cardiac outcomes of cancer therapies become increasingly prevalent, an integrated approach to trial design and clinical management is needed.